Prevalence of pelvic floor disorder and associated factors among women in Arba Minch Health and Demographic Surveillance Site, Gamo Zone, Southern Ethiopia, 2021 - Kebede, Berhanu Negese; Hayelom, Desta Haftu; Birgoda, Gebremaryam Temesgen; Yimer, Awol Arega; Mesfin, Bezawit Afework; Tetema, Mesfin Difer; Alemu, Solomon Seyife; Getahun, Kassaw Beyene (Frontiers in Urology, 2023)
Background Globally, millions of women develop pelvic floor disorder. It imposes a considerable emotional, social, and financial burden on women’s lives. Despite this, in developing countries, nearly half of women with pelvic floor disorder do not seek any help due to feelings of isolation, depression, shame, and loss of control. Thus, the magnitude of the problem is largely unknown. The aim of this study was to assess the prevalence of pelvic floor disorder and associated factors among women at Arba Minch Health and Demographic surveillance site. Methods A cross-sectional study with a simple random sampling technique was employed on a community basis. The data were entered into EpiData version 3.1 and then exported to Statistical Package for Social Sciences version 25 for data cleaning and analysis. Bivariate and multivariable analyses using binary logistic regressions were carried out to identify factors associated with pelvic floor disorder. The level of significance was declared at a p-value of < 0.05. Results The prevalence of pelvic floor disorder was 31.4% (95% CI = 26.9% to 35.8%). Being grand multiparous (AOR = 3.919, 95% CI = 1.495–10.276), having a history of instrumental delivery (AOR = 3.042, 95% CI = 1.483 to 6.241), having a history of perianal tearing (AOR = 2.972, 95% CI = 1.491 to 5.927), and having a medical disease (AOR= 2.698, 95% CI = 1.526 to 4.770) were factors associated with pelvic floor disorder. Conclusions and recommendations The prevalence of pelvic floor disorder was high in the study area. Parity, instrumental delivery, perianal tears, and medical problems were factors affecting the prevalence of pelvic floor disorder. There is a need for an improvement of policies and strategies focusing on prevention and treatment services to alleviate the problem.